Competent non-native users of English? Requestive behavior of Norwegian EFL teachers - Krulatz, Anna (Nordic Journal of English Studies, 2016)
This paper reports the results of a study of English requests produced by Norwegian EFL teachers. The data were collected using a discourse completion task consisting of four scenarios eliciting high and low imposition requests. Head acts of requests and internal and external modifications were analyzed. The findings reveal a complex requestive behavior and sensitivity to the social context of the interaction and suggest that the teachers in the study have developed advanced pragmatic competence.